Elective Orthopaedic Surgery During COVID-19: A Safe Way to Get Back on Track. Issue 4 (October 2020) - Zorzi, Claudio; Piovan, Gianluca; Screpis, Daniele; Natali, Simone; Marocco, Stefania; Iacono, Venanzio
Abstract : Background: The novel coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has greatly changed our way of living and working. We have developed a method to treat urgent patients in a safe way, and we applied the same protocol to resume elective surgical procedures. Methods: We reorganized the system and the management of our orthopaedic department to perform elective surgical procedures in a safe way. During the COVID-19 lockdown, 614 patients underwent elective orthopaedic procedures. Results: No major postoperative complications were recorded. None of the orthopaedic surgeons, health-care personnel, or hospitalized patients was infected in this period of activity. Conclusions: During COVID-19, it is possible to perform elective surgical procedures in a safe way.